Epidemiological Characteristics of Leprosy in China, 2018 - Le Wang; Pei-Wen Sun; Mei-Wen Yu; Heng Gu; Hong-Sheng Wang; Xiang-Sheng Chen (Wolters Kluwer Health, 2020)
Abstract. Objective:. To describe the epidemiological characteristics of leprosy in China in 2018 and provide the essential evidences for leprosy control. Methods:. We collected data of leprosy cases nationwide from Leprosy Management Information System in China (LEPMIS) except Hong Kong, Macao, and Taiwan. And then we performed a descriptive and comparative analysis. Results:. A total of 521 new leprosy cases were detected nationwide in 2018, with a case detection rate of 0.037/100,000. The proportion of children under 15 years of age, multi-bacillary (MB) cases, and cases with WHO grade 2 disability (G2D) were 1.3%, 89.4%, and 19.0%, respectively. There were 2,479 registered cases of leprosy in China by the end of 2018, accounting for a prevalence rate of 0.178/100,000, with 43 replase cases. Southwest China separately accounted for 312/521 (59.9%) newly detected cases and 1180/2479 (47.6%) registered cases of leprosy in China. Conclusion:. China is a low endemic country for leprosy and the detection rate was much lower than the global average. Southwest China is still the key regions for leprosy control, including Yunnan, Guizhou, and Sichuan. In addition, leprosy in low endemic provinces also needs to be focused.